Two new species of Phyllocladus (Coleoptera: Pyrochroidae: Pyrochroinae) from China, with a key to males of the Chinese species - Young, Daniel K. (Zootaxa, 2013)
Phyllocladus bilobatus, sp. nov., is described from three males taken in mountainous regions of western Hubei and north-ern Sichuan provinces in central China. All specimens were collected in mid-June at elevations ranging from 1950–2000 meters. Phyllocladus cinnabarus, sp. nov., is described from a single male collected in Jiangkou County, northeastern Gui-zhou province, south-central China. An illustrated key to males of the four Chinese Phyllocladus is presented.